Social Identity and Preferences - Benjamin, Daniel J. (2010)
Social identities prescribe behaviors for people. We identify the marginal behavioral effect of these norms on discount rates and risk aversion by measuring how laboratory subjects’ choices change when an aspect of social identity is made salient. When we make ethnic identity salient to Asian-American subjects, they make more patient choices. When we make racial identity salient to black subjects, non-immigrant blacks (but not immigrant blacks) make more patient choices. Making gender identity salient has no effect on intertemporal or risk choices.